We$1 (Bll paint the octopus red s - Stuve-Bodeen, Stephanie, 1965-; DeVito, Pam (Bethesda, MD : Woodbine House, 1998)
Emma and her father discuss what they will do when the new baby arrives, but they adjust their expectations when he is born with Down syndrome.
"Ages 3-6"--cover p. [4].
Keywords: Down syndrome -- Fiction; People with mental disabilities -- Fiction; Brothers and sisters -- Fiction